2009
DOI: 10.1038/pj.2009.323
|View full text |Cite
|
Sign up to set email alerts
|

Conformational relaxation of single polymer chains confined in a two-dimensional plane studied by scanning near-field optical microscopy

Abstract: The conformational rearrangement of poly(methyl methacrylate) (PMMA) chains confined in a two-dimensional monolayer to a three-dimensional random coil was studied by the shape and segment density analysis of an individual PMMA chain, and was directly observed by scanning near-field optical microscopy. A perylene-labeled PMMA chain was dispersed in the unlabeled PMMA monolayer, after which it was placed on a thick film of unlabeled PMMA and annealed above the glass transition temperature. Although the polymer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It has been reported that PMMA polymer chains at the water interface have high chain mobility although the PMMA bulk is glassy ( T g = ∼100 °C). 25 We hypothesize that the PMEA additive increased the surface chain mobility of the resin surface. The rubbery states of PMEA could contribute to loosening the tight packing of glassy PMMA chains and swelling, thus increasing the chain mobility of surface polymers.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has been reported that PMMA polymer chains at the water interface have high chain mobility although the PMMA bulk is glassy ( T g = ∼100 °C). 25 We hypothesize that the PMEA additive increased the surface chain mobility of the resin surface. The rubbery states of PMEA could contribute to loosening the tight packing of glassy PMMA chains and swelling, thus increasing the chain mobility of surface polymers.…”
Section: Discussionmentioning
confidence: 98%
“…This differs from the conventional method for polymer films in which PMEA and PMMA polymers are dissolved in an organic co-solvent and cast on substrates, followed by evaporation and annealing. 25 It has been previously demonstrated that PMEA migrates to the surface of a PMMA film after annealing at high temperatures above the glass transition temperature ( T g ) of the polymers. However, our resin with PMEA-1 did not show any surface segregation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two dimensional polymeric systems play an important role in our understanding of precursor film spreading, 1 surface lubrication, 2 dynamics of adsorbed polymer chains, [3][4][5][6] and DNA fractionation dynamics. [7][8][9] Extensive experimental, 3,4,6,[10][11][12][13][14][15][16][17][18][19][20] computational and theoretical [21][22][23][24][25][26][27] studies were devoted to static and dynamic properties of polymers at surfaces and interfaces. These studies showed that confinement of macromolecules to surfaces and interfaces can strongly modify not only their conformations, but also their motion and relaxation (see for review ref.…”
Section: Introductionmentioning
confidence: 99%